Gorlin-Goltz syndrome: A rare case - Satyaki Ganguly; Kranti C Jaykar; Rajesh Kumar; Abhijeet Kumar Jha; P K Banerjee (Wolters Kluwer Medknow Publications, 2015)
Gorlin-Goltz syndrome or nevoid basal cell carcinoma syndrome is characterized by multiple basocellular epitheliomas, keratocysts in the jaws, bifid ribs, palmar and/or plantar pits and ectopic calcifications of the falx cerebri. We describe a case of Gorlin-Goltz syndrome illustrating the importance of a thorough examination including the examination of palms and soles and detailed investigations in a patient having lesions suggestive of basal cell carcinoma and multiple naevi.